(untitled) (UBS Scientific Bulletin, 2025)
In this article, using the integrated approach of remote sensing and Geographical Information System (GIS), the Kosonsoy river basin, which is one of the rivers of Northern Fergana, is divided on the basis of a digital elevation model, UBS Scientific Bulletin – Научный Вестник UBS – UBS Ilmiy Axborotnomasi 2024-yil 2-son 81 and the information on the creation of a land use and land cover types map of the basin is presented.